Smooth Metal‐Free Photoinduced Preparation of Valuable 8‐Arylxanthines. Issue 10 (17th June 2019) - Abdulla, Havall Othman; Amin, Ahmed A.; Raviola, Carlotta; Opatz, Till; Protti, Stefano; Fagnoni, Maurizio
Abstract : A set of 8‐arylxanthines was prepared under metal‐free conditions and in aqueous solvents from arylazo sulfones and caffeine or theophylline. Notably, the process took place by simply exposing the reaction vessel to visible or solar light, and unreacted xanthine could be easily recovered during the purification step. Abstract : A set of 8‐arylxanthines was prepared under metal‐free conditions and in aqueous solvents from arylazo sulfones and caffeine or theophylline. Notably, the process took place by simply exposing the reaction vessel to visible or solar light, and unreacted xanthine could be easily recovered during the purification step.